(untitled) (Resunga Journal रेसुङ्गा जर्नल, 2023)
Increasingly, non-English speaking countries in the colossal world use English as the medium of instruction (EMI) to teach academic subjects. English as medium of Instruction (EMI) has been a great issue of discussion in today’s pedagogical field among the concerned stake-holders. This qualitative research aimed to investigate on – English teachers’ perspectives on language shifting in classroom teaching practice (from Nepali to English and again from English to Nepali in 12 years’ time span) in terms of their practice, motivation, challenges and results of the shifting in a secondary school located in a rural setting of Gulmi. For this, three secondary level English teachers were selected purposively and data were collected using in-depth interviews. The results of the study revealed that teachers of the public schools were found aware of the basic concept of the notion of English as a medium of instruction. They were found positive in implementing EMI in conducting their daily teaching and learning activities. The study also showed that teachers of secondary level have been facing different challenges in adopting EMI in the classroom like students’ weak exposure to English, mother tongue interference, unresourceful schools and government policy interference. The study recommended that there should be a favourable and encouraging environment in the public schools for the teachers for adopting EMI in the class. In spite of some challenges of the medium of instruction, they were found to be in favour of the continuation of EMI.